KAJIAN PERAN PUBLIC RELATIONS DALAM MENINGKATKAN CITRA PERGURUAN TINGGI SWASTA DI JAWA TENGAH - Sinatra, Lina; Darmastuti, Rini (Scriptura, 2008)
Nowadays, University as one of the educational institutions is not only paying attention to education but also in getting profit. These are caused by the tight competition among universities. The autonomy system in Government Universities and the establishment of new private universities are the cause of this tight competition. The problem is every private university competes in getting as many students as possible. Individual approach by a professional public relations officer is one of the most effective ways in overcoming this problem. The result of the research shows that not all public relations officers in those private universities, do their role as real public relations officers. They also do not have the same understanding about the role of a public relations officer. The universities which know well about the role of Public Relations, will do their work well and concentrate in building the image for their university. All of these will give influence in the increasing of their student intake but for the ones which do not understand the role of Public Relations will just place Public Relations in the same position as marketing.